School-based victimization in children and adolescents presenting for cognitive behavioural treatment of anxiety disorders. Issue 6 (12th November 2022) - Hunt, Caroline; Bussey, Kay; Peters, Lorna; Gaston, Jonathan; Lo, Alice; Rapee, Ronald M.
Abstract: Background: Peer victimization and anxiety frequently co-occur and result in adverse outcomes in youth. Cognitive behavioural treatment is effective for anxiety and may also decrease children's vulnerability to victimization. Aims: This study aims to examine peer victimization in youth who have presented to clinical services seeking treatment for anxiety. Method: Following a retrospective review of clinical research data collected within a specialized service, peer victimization was examined in 261 children and adolescents (55.6% male, mean age 10.6 years, SD = 2.83, range 6–17 years) with a diagnosed anxiety disorder who presented for cognitive behavioural treatment. Youth and their parents completed assessments of victimization, friendships, anxiety symptoms, and externalizing problems. Results: High levels of victimization in this sample were reported. Children's positive perceptions of their friendships were related to lower risk of relational victimization, while conduct problems were related to an increased risk of verbal and physical victimization. A subsample of these participants ( n = 112, 57.1% male, mean age 10.9 years, SD = 2.89, range 6–17 years) had completed group-based cognitive behavioural treatment for their anxiety disorder. Treatment was associated with reductions in both self-reported anxiety and victimization. Results confirm the role of friendships and externalizing symptoms as factors associated with increased risk of victimization in youth with an anxiety disorder in a treatment-seeking sample. Conclusions: Treatment for anxiety, whether in a clinic or school setting, may provide one pathway to care for young people who are victimized, as well as playing a role in preventing or reducing victimization.